Perencanaan Pengelolaan Lahan Berdasarkan Laju Erosi pada Berbagai Penggunaan Lahan di Kecamatan Wonosalam Kabupaten Jombang: Land Management Planning Based on The Rate Of Erosion in Various Land Uses in Wonosalam District, Jombang Regency - Bagoes Hendrawan, Juve; Purwadi, Purwadi; Arifin, Moch. (Agrocentrum, 2025)
Land use planning must be designed in such a way that the actual rate of soil erosion remains below the permitted erosion threshold. Wonosalam, a sub-district in Jombang Regency, East Java, is characterized by a topography with elevations ranging from 500–600 meters above sea level and predominantly steep to very steep slopes. To estimate erosion rates in this area, the Universal Soil Loss Equation (USLE) method is applied. Based on the erosion rates calculated for various slope units, suitable land management strategies are proposed to reduce soil loss. These strategies are designed to ensure erosion rates do not exceed the tolerable limit. At SPL K3, the erosion rate is already within the allowable limit; however, the planting of Crotalaria is recommended to maintain erosion at 16.1 tons/ha/year. For SPL T1, T2, and T3, the addition of permanent, dense, strip grass barriers and contour planting is advised. At SPL S1, applying 3 tons/ha/year of mulch and implementing contour planting can reduce the erosion rate to 9.6 tons/ha/year. In contrast, erosion rates at SPL Kebun 3, Tegalan 1–3, and Sawah 1 exceed the permissible limit, prompting the need for specific land management interventions. Conservation priorities are established using a scale-based approach, identifying moorlands as the top priority for rehabilitation. Conservation measures include both vegetative and mechanical approaches, such as constructing bench terraces and planting economically valuable crops suited to local conditions—namely coffee and durian—to support sustainable land use and community livelihoods in Wonosalam.